Sistem Penerimaan Mahasiswa Cerdas Baru Berbasis Web - Alfiyudin; Maulana, Irfan; Fitriyani, Anisa; Kasoni, Dian; Aprilyani, Firdha (LPPM STMIK ANTAR BANGSA, 2025)
Abstract—Working memory A number of Indonesian institutions continue to make heavy use of new student admission information systems. But there's a catch: a lot of potential students, particularly those from out of town, have trouble with manual methods and could really use an improved information system. This study employs a system development approach to its research, namely by planning an accessible web-based information system for new student admissions. Using the PHP programming language and the MySQL database server, this new student admission information system was created. This study's findings suggest that a web-based new student admissions information system may streamline the registration process, accept fees, and provide prospective students with all the information they need on new student admissions. Abstrak—Memori kerja Sejumlah lembaga di Indonesia terus memanfaatkan sistem informasi penerimaan mahasiswa baru. Namun, ada kendala: banyak calon mahasiswa, terutama yang berasal dari luar kota, mengalami kesulitan dengan metode manual dan sangat membutuhkan sistem informasi yang lebih baik. Penelitian ini menggunakan pendekatan pengembangan sistem dalam penelitiannya, yaitu dengan merencanakan sistem informasi berbasis web yang mudah diakses untuk penerimaan mahasiswa baru. Dengan menggunakan bahasa pemrograman PHP dan server basis data MySQL, sistem informasi penerimaan mahasiswa baru ini dibuat. Temuan penelitian ini menunjukkan bahwa sistem informasi penerimaan mahasiswa baru berbasis web dapat memperlancar proses pendaftaran, menerima biaya, dan menyediakan semua informasi yang dibutuhkan calon mahasiswa tentang penerimaan mahasiswa baru.